Aboveground net primary production spatio-temporal changes in the bioclimates of Alborz mountains based on multi-sensor satellite data - Marzieh Asgari; Reza Jafari; Mostafa Tarkesh Esfahani; Mahshid Souri (Scientific Reports)
Abstract Aboveground Net Primary Production (ANPP) is a key indicator for assessing the health of rangeland ecosystems. This study estimated ANPP in the central Alborz rangelands of Iran from 2000 to 2020 based on satellite data (MOD13Q1.061, Sentinel-2 L1C), ground-based measurements, along with meteorological data through the Carnegie Ames Stanford Approach model. ANPP trends were ascertained across various bioclimates and vegetation types. A total of 240 sampling sites were selected to measure ANPP using a systematic-random design. Sentinel-2 ANPP values ranged between 2.4 and 44.6 gC/m2 in the study area. The model evaluation, based on the coefficient of determination, indicated a strong relationship between Sentinel-2 derived ANPP and ground data (R² = 0.86, P < 0.01). A significant relationship was also observed between ANPP estimates from the Sentinel-2 and MODIS sensors (R² = 0.8, P < 0.01). The climatic conditions and type of vegetation have a significant impact on rangeland production. The highest annual average ANPP, estimated using MODIS, was 60.57 gC/m2, witnessed in the Psathyrostachys fragilis-Agropyron tauri vegetation type within a humid and cold climate. In contrast, the lowest ANPP, 39.07 gC/m2, was recorded for the Seidlitzia rosmarinus-Artemisia sieberi type in a hyper-arid and cold climate. Generally, the findings demonstrated that integrating modeling approaches with satellite imagery enables robust estimation and analysis of rangeland production dynamics across diverse bioclimates and vegetation types.